Pemberdayaan Pasien HIV dalam Kepatuhan Minum Obat ARV di Yayasan Cakap Peduli AIDS Turen - Tri Nurhudi Sasono; Esti Yunitasari; Ninuk Dian Kurniawati; Nursalam (Jurnal Kesehatan Islam : Islamic Health Journal, 2022)
Abstract. People with HIV-AIDS (PLWHA) are powerless in undergoing ARV treatment programs for the rest of their lives. Compliance with treatment of HIV patients in Indonesia is still a major problem, as evidenced by Lost Follow Up (LFU) for treatment and ART by 21.87%. This decrease in ART adherence ultimately makes patients susceptible to opportunistic infections and has a poor quality of life. The design of this research is pre-post test with control group. The approach used in this study is a non-equivalent control group. The sample used by the purposive sampling technique at the NGO CAKAP AIDS Turen was 48 respondents. Collecting data using a medication adherence question- naire. Statistical test using the Wilcoxon test. The results showed that there was an influence of empowerment with a p-value of 0.017 <0.05 with a coefficient of 0.309. Based on these statistical results, it can be concluded that the empowerment of HIV patients can affect medication adherence